Assessment of cadmium, chrome and lead in Vaccinium corymbosum L. "blueberry" from a market and a supermarket - Villanueva, Meyli (2022)
The objective of this study was to evaluate the determination of cadmium, chromium, and lead in Vaccinium corymbosum L. "blueberry", coming from a market and a supermarket located in the district of Chorrillos-Lima. Due to their condition, in the case of the market, the samples were collected from four points of sale, to obtain a representative sample. In the case of the Supermarket, the sample was unique. By means of the instrumental method of atomic absorption spectrophotometry, the quantification of the heavy metals of cadmium, chromium and lead was carried out, using the atomic absorption spectrophotometer equipment. Concentrations of <0.05 were determined; <0.05; 0.275 ug / gr in cadmium, chromium, and lead, respectively, in blueberries collected from a supermarket and concentrations of <0.05; 0.137; 0.288 ug / gr in cadmium, chromium and lead, respectively, in blueberries collected from a market. The results obtained show that there is a lower concentration of lead in blueberries collected from a supermarket. It is concluded that the concentrations of cadmium, chromium, and lead present in blueberries from a market and a supermarket in Chorrillos were lower than the values ​​established by the European Commission.